Evaluation of the levels of pain and discomfort of piezocision-assisted flapless corticotomy when treating severely crowded lower anterior teeth: a single-center, randomized controlled clinical trial - Omar Gibreal; Mohammad Y. Hajeer; Bassel Brad (BMC, 2019)
Abstract Background No randomized controlled trial (RCT) has compared flapless piezocision-assisted corticotomy in the extraction-based orthodontic decrowding of lower anterior teeth with the conventional treatment in terms of pain, discomfort and acceptability. Therefore, the aim of this trial was to compare piezocision-based orthodontic decrowding of lower anterior teeth following premolar-extraction with the conventional orthodontic treatment regarding levels of pain, discomfort, and patients' satisfaction. Methods A parallel-group RCT was conducted on 34 patients with severely crowded lower anterior teeth. Subjects were randomly allocated to either the experimental (ExpG) or the control group. Piezoelectric corticotomies were performed on the labial surfaces of the alveolar bone in the anterior region in the ExpG. Levels of pain, discomfort, swelling, difficulties of mastication, swallowing and jaws movement limitation were recorded on a Visual Analog Scale (VAS) at 1, 7, 14 and 28 days. In the ExpG, patients were also asked to rate their level of satisfaction following acceleration. Two-sample t tests were employed to detect significant differences. Results No statistically significant differences were found between the two groups at one day following treatment commencement regarding pain, discomfort, difficulties of mastication, swallowing and limitation in jaws movement (P = 0.082, 0.367, 0.062, 0.446, 0.359; respectively). However, a statistically significant difference was found between the two groups regarding the perception of swelling at the first-day assessment (P = 0.011). No statistically significant differences were detected between the two groups at 7 days regarding the five previously mentioned variables. There was a drop down to zero level at two weeks and four weeks following treatment onset for all variables. The level of satisfaction in the ExpG had a mean value of 86.47 (±22.47) and all patients were positive towards recommending the surgical intervention to a friend. Conclusions No significant differences in the levels of pain and discomfort were found between the ExpG and the control group for all variables except for the perception of swelling at one day following intervention. Patient-centered outcomes revealed a high level of acceptance and satisfaction with this technique. Trial registration This trial was registered at Clinical Trials.gov (Identifier NCT02975765).